Mediating Role of Social Support in Resilience and Quality of Life in Patients with Breast Cancer: Structural Equation Model Analysis - Gulden Kucukakca Celik1; Hatice Çakır; Engin Kut (Elsevier, 2021)
Objective: This study aimed to investigate the mediating role of social support in the relationship between resilience and quality of life (QoL) among Turkish patients with early-stage breast cancer. Methods: The study used a descriptive and cross-sectional design and was carried out in the oncology ward of a hospital in the Central Anatolia region of Turkey. A demographic-disease survey, the Turkish version of the Connor-Davidson Resilience Scale 25, the Multidimensional Perceived Social Support Scale, the European Organization for Research and Treatment of Cancer QoL Questionnaire Core, and the QoL Questionnaire Breast Cancer 23 were used to interview 113 patients with breast cancer. Results: Social support played a partial mediator role in the relationship between resilience and functional QoL. There was a negative correlation between functional QoL Questionnaire Breast Cancer 23 and psychological resilience and social support (P < 0.005). The mediation effect ratio was 10.2% (R2 = 0.102). Social support was found to not have a mediating role in the relationship between psychological resilience and general QoL (P < 0.05). Conclusions: Patients do not want social support to end, and their weakness in the eyes of others may have a negative impact on their QoL and resilience.